2016
DOI: 10.1080/1369183x.2016.1166040
|View full text |Cite
|
Sign up to set email alerts
|

East-European immigrants responding to the recession in Britain: is there a trade-off between unemployment and over-qualification?

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Using data generated between 2012 and 2014 from a qualitative study of Eastern European migrants in the UK, we draw further attention to how migrants access, maintain and construct social networks in the host country (Ryan 2011), focusing on the flow of resources not only within social networks in the UK but also, crucially, across transnational spaces between the UK and Eastern Europe. Over the past decade, increasing numbers of 'new' migrants have arrived in the UK (Jones et al 2014) because of the rise in refugees and asylum seekers from war-torn countries (Edwards et al 2016), as well as migration from the new EU member states (Ciupijus 2011;Khattab and Fox 2016) and other European countries such as the former Soviet states of Ukraine, Russia, Belarus and Moldova. Despite the growth of 'new' migrant communities in the UK, forming part of the 'age of super-diversity' (Meissner and Vertovec 2015;Vertovec 2007Vertovec , 2014, such groups have rarely figured in contemporary debates on self-employment and/or entrepreneurship, other than in a few notable studies (Barrett and Vershinina 2017;Edwards et al 2016;Ram et al 2008).…”
mentioning
confidence: 99%
“…Using data generated between 2012 and 2014 from a qualitative study of Eastern European migrants in the UK, we draw further attention to how migrants access, maintain and construct social networks in the host country (Ryan 2011), focusing on the flow of resources not only within social networks in the UK but also, crucially, across transnational spaces between the UK and Eastern Europe. Over the past decade, increasing numbers of 'new' migrants have arrived in the UK (Jones et al 2014) because of the rise in refugees and asylum seekers from war-torn countries (Edwards et al 2016), as well as migration from the new EU member states (Ciupijus 2011;Khattab and Fox 2016) and other European countries such as the former Soviet states of Ukraine, Russia, Belarus and Moldova. Despite the growth of 'new' migrant communities in the UK, forming part of the 'age of super-diversity' (Meissner and Vertovec 2015;Vertovec 2007Vertovec , 2014, such groups have rarely figured in contemporary debates on self-employment and/or entrepreneurship, other than in a few notable studies (Barrett and Vershinina 2017;Edwards et al 2016;Ram et al 2008).…”
mentioning
confidence: 99%
“…The expected wage differences have been consistently observed for CEE immigrants (with a focus on the UK: Dustmann et al 2010;Johnston et al 2015;Pietka et al 2013;Trevana 2013). Consequently, the intra-EU differentials in wages and potentially also portable unemployment benefits (Bruzelius et al 2017) seem to increase the likelihood of EU immigrants from poorer member states taking on lower paid and lower skilled jobs (Khattab & Fox 2016). In line with very high unemployment rates and more limited welfare state cushioning as push factors, Spreckelsen et al (forthcoming) and Akgüc and Beblavý (forthcoming) find poorer qualitative labour market outcomes for young immigrants from the EU-South as compared to the EU-West in North-Western destination countries.…”
Section: Labour Market Segmentation Of Immigrants In Western Europe: mentioning
confidence: 89%
“…These differences will enable immigrants from more affluent countries (EU-West/EEA) − in contrast to immigrants from poorer countries − to look on average for a longer period of time for suitable jobs and to move only when they can be sure of getting a good match. CEE immigrants, by contrast, will be more inclined to take up jobs in the destination country that are low-wage and low-skilled and for which they are over-qualified (Khattab & Fox 2016).…”
Section: Recent Research Focuses Almost Exclusively On the Labour Marmentioning
confidence: 99%
See 1 more Smart Citation
“…However, losing one's job is not the only impact that a recession may have on individual workers, and during such times immigrants may be willing to accept jobs well below their qualification (Khattab & Fox, 2016). In the WIE data, the respondents who reported that they had suffered from the economic downturn were a minority: only 16 per cent explained that their position is worse in comparison with the pre-crisis situation in the spring of 2008.…”
Section: The Situation Worsenedmentioning
confidence: 90%